THE INFLUENCE OF ASYMMETRIC INFORMATION ON FOREIGN CAPITAL INFLOWS IN ASEAN PLUS THREE COUNTRIES - Mohd Hasimi Yaacob; Raihan Ashikin Mohd Nor; Hawati Janor; Noor Azuan Hashim (International Journal of Management Studies, 2021)
This paper examines the influence of asymmetric information on foreign capital inflows in ASEAN PLUS THREE (ASEAN+3) countries. Linking capital flows to stock market setting, it substantiates other efforts concerning the debatable issues of the effect of asymmetric information on foreign direct investment (FDI) and foreign portfolio investment (FPI). The asymmetric information is captured through the stock market microstructure perspective on the width and depth dimensions using highly frequency cross sectional data from year 2000 to 2015. Roll and Amivest models are employed to quantify the width and depth aspects of the asymmetric information. Employing the panel data technique, the results demonstrate the significant effect of market transparency on foreign capital inflows specifically the FDI as compared to the FPI. An increase in the width and depth analysis based on the Amivest model signifies a high informational transparency, thus shows a lower asymmetric information which consequently leads to the high foreign capital inflows. The results of the study provide information to the policymakers in monitoring capital inflows on the aspect of market transparency and highlight the importance of the stock market microstructure in assessing the asymmetric information for ASEAN+3 countries.